The Chemical Studies of Zizyphus jujuba - KHAN, MOHSIN ALI; NIZAMI, SHAIKH SIRAJUDDIN; KHAN , SHAHZAD AHMAD (Biological Sciences - PJSIR, 2022)
Furthermore, following vague hints in older literature that the fruit also contains 2.73-6.43% protein [11,12], the aqueous and cthanolic extracts were exhaustively studied to verify the presence of protein. The various techniques employed for this purpose included: